Land Administration Policy In Bantul and Sleman Districts - Subekti Widiyasno; Dyah Mutiarin; Herdin Arie Saputra; Ikhwan Rahmatika Latif (Journal of Government and Civil Society, 2020)
The collection of land belonging to the Yogyakarta Palace or Sultan Ground (SG) and the Paku Alaman Duchy or Paku Alam Ground (PAG) land has been slow due to overlapping regulations. The collection of Sultan Ground and Paku Alam Ground land which is regulated in the Privileges Act is hampered by changes in the status of land ownership at the village level which belongs to the state and individuals. The certification process by the National Land Agency cannot be carried out yet. This data collection is based on Special Region Regulation No. 1 of 2017 concerning Management and Utilization of Sultanate Land and Duchy Land. The purpose of this study was to analyze land management policies in sustainable areas in the regencies (four) villages in Bantul Regency and Sleman Regency. This type of research conducted by the author is a mixed/mixed research (mixed methodology). Data analysis techniques in this study used the Nvivo 12 Plus software, processing by using the Crosstab Query Analysis, Cluster Analysis, Comparasis Diagram Analysis features. The results of research in land management are still not carried out correctly and evenly. Several problems were encountered, such as the absence of road access, missing land boundaries, land parcels occupying other community lands, and conflicts. Pendataan tanah milik Keraton Yogyakarta atau Sultan Ground (SG) dan tanah Kadipaten Paku Alaman atau Paku Alam Ground (PAG) berjalan lambat karena terkendala aturan yang tumpang tindih. Pendataan tanah Sultan Ground dan Paku Alam Ground yang diatur dalam Undang-Undang Keistimewaan terganjal oleh perubahan status kepemilikan tanah di tingkat desa yang menjadi milik negara dan perorangan. Akibatnya proses sertifikasi oleh Badan Pertanahan Nasional belum bisa dilakukan. Pendataan ini dilandasi Peraturan Daerah Istimewa No 1 Tahun 2017 tentang Pengelolaan dan Pemanfaatan Tanah Kasultanan dan Tanah Kadipaten. Tujuan penelitian ini untuk menganalisis kebijakan penataan pertanahan di kawasan berkesinambungan di 4 (empat) desa di Kabupaten Bantul dan Kabupaten Sleman. Jenis penelitian yang dilakukan oleh penulis adalah penelitian campuran/kombinasi (mixed methodology). Teknik analisis data dalam penelitian ini menggunakan software Nvivo 12 Plus, mengolah dengan menggunkan fitur Crosstab Query Analysis, Cluster Analysis, Comparasison Diagram Analysis. Hasil penelitian dalam penataan pertanahan masih belum dilakukan secara baik dan merata, terdapat beberapa permasalahan yang dijumpai seperti tidak adanya akses jalan, batas tanah yang hilang, bidang tanah menempati wilayah tanah masyarakat yang lain, dan konflik.